Histomorphological Examination of Age-Related Change in Rat Esophagus and Stomach - Taşlıdere, Elif; Kuruş, Meltem; Kazancı, Alper; Otlu, Ali (Fırat University, 2013)
Objective: In this study, it was aimed that age-related morphological changes in rat esophagus and stomach was investigated with light microscopy. Materials and Methods: In this study, 21 female Sprage-Dawley rats were used. Rats were divided into three groups as follows. Group1:21 days old, Group2:2 month old and Group3:19 month old. At the end of the examination esophagus and stomach tissues were removed.The sections stained wiht hematoxylin-eosin and evaluated light microscopically. Results: The mean thickness of esophagus epithelium was measured. It was 31.85±5.7 μm in Group1, 40.95±6.7 μm in Group2 and 44.68±9.2 μm in Group3. The mean thickness of tunica muscularis in esophagus measured. It was 128.9±23.1 μm in Group 1, 207.8±38,5 μm in Group2 and 256.07±35.52 in Group3. We observed that the thickness of esophagus epithelium and tunica muscularis were significantly increased by age in all groups (p

Amaç: Bu çalışmada sıçan özefagus ve midelerinde yaşa bağlı olarak gelişen morfolojik değişikliklerin ışık mikroskobik açıdan incelenmesi amaçlandı. Gereç ve Yöntem: Çalışmamızda 21 adet dişi Spraque-Dawley sıçan kullanıldı. Sıçanlar, Grup 1: 21 günlük sıçanlar, Grup 2: 2 aylık sıçanlar ve Grup 3: 19 aylık sıçanlar olmak üzere 3 gruba ayrıldı. Deney sonunda çıkartılan özefagus ve mide dokuları rutin histolojik doku takibinden sonra parafine gömüldü. Kesitler Hematoksilen-eozin ile boyanıp ışık mikroskobunda incelendi. Bulgular: Çalışmamızda özefagus epitel kalınlığı Grup 1'de ortalama 31.85±5.7 μm, Grup 2'de 40.95±6.7 μm, Grup 3'de 44.68±9,2 μm olarak bulundu. Tunika muskularis kalınlığı Grup 1'de ortalama 128.9±23.1 μm, Grup 2'de 207.8±38.5 μm ve Grup 3'de 256.07±35.52 μm olarak tespit edildi. Sıçanlarda özefagusa ait epitel ve tunika muskularis kalınlığı ölçüldüğünde yaşlanmaya bağlı olarak kalınlığın anlamlı derecede arttığı gözlendi (p
Sıçanlarda Özefagus ve Midede Yaşa Bağlı Değişimlerin Histomorfolojik Açıdan İncelenmesi